HIGHER EDUCATIONAL INSTITUTIONS PSYCHOLOGICAL FACTORS FOR IMPROVING THE EFFECTIVENESS OF CREATIVE INNOVATIVE TRAINING IN EDUCATIONAL ACTIVITIES (Web of Teachers: Inderscience Research, 2025)
This article explores the psychological factors that contribute to enhancing the effectiveness of creative and innovative training in higher educational institutions. It examines the role of motivation, cognitive flexibility, emotional intelligence, and learning environments in fostering creativity and innovation. The study utilizes empirical methods to assess the impact of these psychological aspects on students' learning outcomes. The findings suggest that integrating psychological principles into educational strategies significantly improves students' engagement and innovative capabilities.